Pengaruh Disiplin Kerja Terhadap Kinerja Perangkat Desa Di Desa Sindangherang Kecamatan Panumbangan - Adi Robith Setiana Adi (LP2M Universitas Perjuangan Tasikmalaya, 2022)
This study aims to find out; 1) Work discipline of Village Devices in Sindangherang Village, 2) Performance of Village Devices in Sindangherang Village, 3) The Influence of Work Discipline on The Performance of Village Devices in Sindangherang Village. The method used in this study is a descriptive quantitative method with a type of case study. The data used in this study are primary data and secondary data. The population and samples in this study were as many as 10 people using total sampling techniques. The analysis techniques in this study use simple regression analysis and hypothesis test using t test. The results of the study showed that ; 1) The working discipline of Village Devices in Sindangherang Village is in excellent classification, 2) The performance of village devices in Sindangherang village is in excellent classification, 3) The influence of the work discipline of Village Devices in Sindangherang Village has a significant positive influence on the performance of Village Devices in Sindangherang Village. Keywords : Work Discipline, Performance